2010
DOI: 10.1080/10538711003789031
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Child Sexual Abuse—A Qualitative Interview Study with Representatives of the Socio-Legal System in Urban Tanzania

Abstract: Through in-depth interviews, this study explored perceptions and experiences of key players handling child sexual offense cases in Dar es Salaam, Tanzania. The informants included public police investigators, magistrates, legal workers, and social workers working with nongovernmental organizations. The interviews were recorded, transcribed verbatim, and analyzed using qualitative content analysis. Five themes emerged summarizing factors associated with sexual offenses, including community passivity, legal syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
5
13
0
Order By: Relevance
“…Corruption, for example, could prevent a woman from accessing justice if the perpetrator had the means to “pay off” the police or local government officials. This finding, which is in line with a study of CSA done in a semi-urban area in Tanzania [35], contributed to the low rate of help-seeking observed among women and children. The present study illustrates how the responses of criminal justice professionals affect not only prosecution, but also influence whether a woman reaches out to other support services as well.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Corruption, for example, could prevent a woman from accessing justice if the perpetrator had the means to “pay off” the police or local government officials. This finding, which is in line with a study of CSA done in a semi-urban area in Tanzania [35], contributed to the low rate of help-seeking observed among women and children. The present study illustrates how the responses of criminal justice professionals affect not only prosecution, but also influence whether a woman reaches out to other support services as well.…”
Section: Discussionsupporting
confidence: 89%
“…If a woman is raped, it is her reporting of the rape that brings dishonor and shame rather than the violent act itself. These findings are supported by other studies in urban Tanzania where dimensions of social stigma related to sexual violence affect social interactions [33,35,36]. At an individual level, the current study shows that if you are in a marriage, you are forced to remain in that relationship even when you are abused, simply because of the fear of being blamed for disclosing affairs internal to the relationship, but also because marital rape is not recognized by Tanzanian law.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In community- and hospital-based studies among community groups and health care workers in Tanzania, it was found that apart from seeking medical and legal care, rape survivors who report to local government leaders and health facilities often do so in order to obtain opinions on legal or social procedures to follow and to establish the seriousness of the events [27-29]. It was further shown that the consequences of rape and CSA are not well understood by the community, including health care workers [27-29]. It has been shown that community reactions to these victims are important predictors of the long-term consequences of rape and CSA [28,30,31].…”
Section: Introductionmentioning
confidence: 99%